Development of a linear algebra website for teaching and learning - Halim, Suhaila Abd; Hadi, Normi Abdul; Hamdan, Nur Izzati (AIP conference proceedings, 2024)
Teaching and Learning Mathematics in the 21st centuries highly related to the digital technology used in the classroom. Mathematics is the best practice in the standard teaching and learning (T&L) process where the teacher and student physically attend the class. There is where the interaction and discussion on subject matter happened. However, due to the COVID-19, the practice needs to be changed drastically in which both sides of teacher and student are not allowed to have a physical class to avoid any contact. The learning process must proceed and adapt well to the current situation. A Learning Management system must be developed as a platform to digitally organize educational material. Due to that, this paper aims to illustrate the development of a website that is beneficial in T&L Mathematics courses. The content of the mathematics course chosen is Linear Algebra. There are various learning management systems, but the one that customizes the purpose and requirement of our class content can be developed by ourselves. Google offers a good package where google sites can be easily set up for that purpose. The content is arranged according to based on topics. In addition, the interactive learning environment is also embedded in developing the system to attract the student’s attention during class hours. Live chat is also provided for the student to ask questions at their convenience time. Developing a customized learning management system can be an alternative for teachers to provide a digital environment to their students so that the process of T&L can be continued. Our website has been introduced to students, and their feedback is recorded. The result shows that students show positive responses while describing the website